Digital Literacy as a Response to the Threat of Radicalism in Islamic Education (PAI) Learning in Secondary Schools - Intan Nur Aini; Nur Aisyah (JURNAL ISLAM NUSANTARA, 2025)
This study aims to analyze the role of digital literacy in responding to the threat of radicalism in Islamic Religious Education (PAI) at the secondary school level. Using a qualitative case study approach across several schools in Bondowoso, data were collected through interviews, observations, and documentation. The findings show that digital literacy is not only related to technical skills but also encompasses critical awareness of how to select and evaluate religious information to avoid exposure to radical ideologies. Islamic education teachers play a crucial role by curating digital content, using interactive media, and facilitating reflective discussions to instill the values of religious moderation. The challenges identified include limited infrastructure, uneven digital competence among teachers, and insufficient support for school policies. Overall, the integration of digital literacy into Islamic Religious Education plays a strategic role in shaping critical, tolerant, and moderate attitudes as a preventive measure against radicalism in educational settings.